Immunization with Streptococcus suis bacterin plus recombinant Sao protein in sows conveys passive immunity to their piglets. Issue 1 (December 2016) - Hsueh, Kai-Jen; Cheng, Li-Ting; Lee, Jai-Wei; Chung, Yao-Chi; Chung, Wen-Bin; Chu, Chun-Yen
Abstract Background Streptococcus suis (S. suis ) causes arthritis, meningitis, septicemia, and sudden death in pigs and is also an zoonotic agent for humans. The present study demonstrated that immunization with recombinant Sao-L (surface antigen one-L, rSao-L) protein from a strain ofS. suis serotype 2 in pigs was able to increase cross-serotype protection againstS. suis serotype 1 and 2 challenge. Since weaning piglets are more susceptible toS. suis infections due to the stresses associated with weaning, prepartum immunization in sows may convey passive immunity to piglets and provide protection. Results Pregnant sows were immunized with a vaccine containing inactivatedS. suis serotype 2 plus rSao as the antigens. Blood samples were collected from their piglets after birth for analysis of antigen-specific antibody titers and levels of various cytokines. Results demonstrated that the titers ofS. suis and rSao-specific antibodies were significantly (p < 0.05) higher in the vaccinated piglets in comparison with that of piglets in the control group. The serum levels of interferon (IFN)-γ, interleukin (IL)-4, IL-6, and IL-12 were significantly (p < 0.05) increased in piglets born from vaccinated sows when compared to piglets from unvaccinated sows. In addition, piglets were challenged by heterologous and homologousS. suis . All piglets from unvaccinated sows developed severe symptoms of bacteremia, fever, anorexia, depression, and arthritis. On the other hand, piglets from vaccinated sows had significantly (p < 0.05) reduced clinical symptoms and lesion score (by 75 and 81%). Conclusions Our results revealed that immunizing pregnant sows with the vaccine containing inactivatedS. suis bacterin plus rSao as the antigens is able to enhance passive immunity against heterologous and homologousS. suis challenge in their piglets.